Estilos de vida de mujeres en edad fertil y su influencia en el riesgo laboral en una empresa agroindustrial de La Libertad - Quispe Chávez, María Milagros (2015)
This research work is quantitative, cross and correlational Design Association causal., was carried out with the sole purpose of determining the influence of the lifestyles of women in fertile age in the occupational hazard in an agro-industrial company of La Libertad, the sample was formed by 102 women (aged 19 to 49) of different areas of the company with a predominance of age. A questionnaire was used in the development of the research work, likewise direct observation for the application of the instruments; 3 were instruments for the collection of data between open and closed to measure questions the reliability of the instrument was obtained for the total scale a Cronbach's alpha of 0.794 reliability index, which indicates that the scale for measuring the lifestyle is reliable. It can be seen that a majority of women have no healthy lifestyle (62.7%) in an agro-industrial company of La Libertad. A tendency to present events with a level of trivial occupational hazard (38.2%) mostly in women of childbearing age. A highly significant influence of the dimensions of the styles of life in the occupational hazard in women of childbearing age. Also shows that the five dimensions independent and with higher degree of relationship with the risks explained 94.9% of the variability in the level of occupational risk. Shown that the marital predominates mostly as free union (29.4%) as the female housekeeper a (40.2%) receiving their income between 100599 soles with a (49%) and then secondary primary education (33.3%) with religion who profess the Catholic (57.8%).